PELAKSANAAN TANGGUNGJAWAB PENGURUS KOPERASI TERHADAP PINJAMAN ANGGOTA DAN FAKTOR YANG MEMPENGARUHI DITINJAU DARI UNDANG-UNDANG NOMOR 17 TAHUN 2012 TENTANG PERKOPERASIAN PADA KSP KOPDIT PINTU AIR CABANG KUPANG - Lasibey, Misye Liliyani; Usman, Siti Ramlah; Pello, Helsina F (Petitum Law Journal, 2023)
Cooperatives are one form of economic organization that is getting government attention. A cooperative is an incorporated organization. Cooperative development in Indonesia is part of the overall national development effort. The benefits of this research are: 1) Theoretically, this research can bring new vehicles in building insights in the academic scope as well as a stage of enrichment on theories and for further research can be used as a reference for similar research as information material for cooperative administrators in carrying out their responsibilities. 2) As information material for cooperative members to find out obstacles in the implementation of management responsibilities. The results of this study show that the implementation of the responsibilities of the cooperative management against the loan of cooperative members has been going well, but it has not been maximized where the cooperative teachers in charge of providing convoluted explanations to cooperative members have not all been able to understand the existing explanations. Factors that affect the implementation of the responsibilities of the cooperative management are economic factors that become obstacles in terms of loan installment repayment. In addition, misusing loans for things that deviate from their use.